DRAMATURGIA EM DIÁLOGO: MECANISMOS INTERTEXTUAIS ENTRE CATO A TRAGEDY IN FIVE ACTS, DE JOSEPH ADDISON, E CATÃO, DE ALMEIDA GARRETT - Carvalho, Carolina Filipaki de (2017)
This research aims to analyze the intertextual relations between the homonymous literary oeuvre Cato, published by Joseph Addison, in 1713, in England, and Almeida Garrett, in 1822, in Portugal. The Portuguese writer admitted that he was inspired by the English work to conceive his own. Therefore, it was investigated in this dissertation the factors that approximate the two dramas in an intertextual perspective, which is based on the studies of Kristeva (1969), Bouché (1974), Genette (1982), Sant'Anna (1985) and Hutcheon (1991), among other scholars. The theoretical framework raises questions related to Comparative Literature, through the approach addressed by Nitrini (2000) and Carvalhal (2010). The comparison between the texts revealed that the two authors were socially engaged and that the plays were written with the intention to promote the allegory of the political moments experienced by the authors in their own countries. It was concluded that the play written by Garrett, for its intertextual dialogue with the intention of emulating Addison’s play, is a stylization of the English drama. In addition to the usual intertextual mechanisms, like the citation and allusion, five mechanisms described by Bouché (1974), as characteristic of the parody, were found in the stylized text and received a new nomenclature: stylizing paraphrasic addition; stylizing translocution; stylizing suppression; stylizing suppressive translocution and stylizing suppressive fragmentation.